(untitled) (Research, Society and Development, 2021)
Learning Natural Sciences in the Early Years of Elementary School is often a pending subject in the life of our classrooms, as most of the knowledge covered at this stage always starts from a social perspective. It is important to take into account the cognitive capacity of students for this type of abstract knowledge, prior knowledge about the subject and motivation throughout the teaching-learning process. These factors will determine the effectiveness or not of the knowledge acquired by the students. The main objective was to describe and analyze the characteristics of the teaching of Natural Sciences at that level of education. This study is justified by the relevance of the level of initial education and science teaching at this stage, taking into account that it includes children at a stage characterized by curiosity and the desire to know the world. This justification is also supported by the fact that there is little information about science teaching in the early grades of elementary school.